The Effect of Regional Original Income, General Allocation Funds, And Results Sharing Funds on Capital Expenditure Allocation with Economic Growth as Moderating Variables in East Java Regency/City Government 2013-2015 - Cahyaning, Sri (Jurnal Ilmu Ekonomi Terapan, 2018)
This study aims to examine and analyze the effect of Regional Original Income, General Allocation Funds, and Revenue Sharing Funds on Capital Expenditures and the effect of Regional Original Income, General Allocation Funds, and Revenue Sharing Funds with moderating economic growth on Capital Expenditures. This research was conducted at the Regency/City government in East Java Province. The sampling technique used is saturated sampling, and there are 36 districts/cities of East Java as the sample of this study. This study uses the APBD Realization Report and the GRDP Table for the 2013-2015 period as samples. The analytical method used to test the hypothesis in this study is Moderated Regression Analysis (MRA). The results of this study indicate that Regional Original Income, General Allocation Funds have an effect on capital expenditures in the Regency/City of East Java Province, but the Profit Sharing Fund variable has no effect on capital expenditures. The moderating variable (economic growth) is able to moderate the Profit Sharing Fund variable, but is not able to moderate the Regional Original Income and General Allocation Fund variables on capital expenditures.